PTH-045 Minimally invasive proctocolectomy and ileal pouch-anal anastomosis: an attractive management option for patients with ulcerative colitis. (22nd June 2015) - Ahmed, J; Stefan, S; Goh, N; Flashman, K; Khan, J; Parvaiz, A
Abstract : Introduction: Restorative proctocolectomy and Ileal pouch-anal anastomosis (IPAA) is the standard procedure for patients with ulcerative colitis (UC), refractory to medical treatment. Recently, there has been increased interest in the use of laparoscopy and robotic approaches for the management of these patients, due to associated benefits of minimal access techniques. Minimally invasive 2 or 3 stage restorative proctocolectomy and IPAA is technically challenging and performed in specialised centres. Aim of this study was to assess the feasibility and short term outcomes of this procedure in a specialist unit. Method: Prospectively collected data related to 52 consecutive patients who underwent restorative proctocolectomy and IPAA, from June 2008 to February 2015, was analysed. Results: Male were 32 (61%) and median age was 37 years (range – 18–68) with median BMI of 25 (range –17–38). 39 (75%) patients had previous surgery. 15 (28%) underwent panproctocolectomy and IPAA, whereas 37 (78%) patients had a 3-stage procedure. Median operating time was 220 (range – 135–480) minutes. 4 (2.8%) cases were performed with robotic approach whilst one case (1.9%) was converted to open in laparoscopic group. No intra-operative complication was recorded. All patients had a defunctioning ileostomy fashioned to protect pouch anal anastomosis. Median length of stay was 7 (range – 3–38) days. 30 days mortality, reoperation and anastomotic leak was none however 13 (25%) patients had readmission within 30days. The most common causes for readmission were abdominal pain and high stoma output. Conclusion: Minimally invasive restorative proctocolectomy and IPAA is safe and attractive option. It has shown good short term outcomes, and offers the benefit of better cosmesis and short hospital stay. Disclosure of interest: None Declared.